Risks and risk management of kandy city wastewater management project (KCWMP) - Dasanayaka, D.M.T.; De zoysa, M. (University of Jaffna, 2020)
This research's objectives were to identify the risks related to the Kandy city wastewater management project and apply the risk assessment, risks prioritization, and risks preventive strategies to suggest appropriate mitigation measures, based on the risk management process. A structured questionnaire was prepared and gathered relevant data as primary information with a convenience sampling method. All the collected data and observed information based on risks identification were analyzed and explained the overall risk factors, using three dimensions; risk impact, risk probability and risk discrimination. The progress of risk prioritization and risk preventive action was evaluated by comparing the risk identification steps. According to the risk prioritization the significant risk types are identified as: resource delay, change project design according to the construction site, failure to meet cost estimate, the design is not fit for the purpose and low team motivation. To obtain the project's expected final quality, the major risks should be mitigated withby, choosing stable suppliers, providing resources on time, updating initial agreement, making design according to the project scope and project site, and making fixed-price contracts and motivating project members.
Keywords: Project; Risk assessment; Risk management and risk prioritization